Intimate Partner Violence and Psychological Maladjustment: Examining the Role of Institutional Betrayal Among Survivors - Lee, Jenny Y. (Journal of interpersonal violence, 2021)
Research has found that a majority of individuals, irrespective of gender, experienced their first intimate partner violence (IPV) victimization between the ages of 18 and 24 years. Indeed, researchers have found that college students’ experiences of IPV are comparable if not higher than that of the general population. IPV victimization also places individuals at a higher risk for developing psychological conditions. In addition, when IPV experiences occur on college campuses, there are a variety of institutional factors that may impact the outcome of the traumatic event for the survivor. The present study seeks to examine whether institutional betrayal moderates the relationship between IPV and different psychological outcomes (i.e., depression, posttraumatic stress, anxiety). The study analyzed survey responses from a sample of 316 undergraduate students attending a Midwestern University. Three separate hierarchical regression analyses were conducted for each of the maladaptive psychological outcomes. Results showed that institutional betrayal was positively correlated with depressive symptoms, posttraumatic stress symptoms, and anxiety symptoms. Interestingly, institutional betrayal was a significant predictor of depressive symptoms, posttraumatic stress symptoms, and anxiety symptoms when controlling for the effects of physical violence, sexual violence, and psychological aggression. The present study highlights the significance of the impact of institutional betrayal, independent of interpersonal betrayal, on mental health.